Development of Internal Marketing with Dynamic Systems Approach in Utilities (Case Study: Wuhan Fiberglass International Technology Company) - Alireza Mirzaei Qatarollar; Hassan Saberi; Hamid Reza Saidnia (تحقیقات کاربردی علوم جغرافیایی)
Previous research has acknowledged the importance of human resources in service companies by influencing the end customer and has shown that if internal marketing succeeds, external marketing will also develop, but describing this development is beyond the reach of purely quantitative or qualitative studies. . In this regard, simulation can come with the help of the humanities and identify the factors influencing the development of internal marketing. In this study, using the systems dynamics approach, factors affecting the success of internal marketing were investigated. The statistical population is all marketing experts at Fiberglass. Primary data were obtained through interviews with them and secondary data from company documentation. Dynamic drawing and modeling and final loop identification through VENSIM PLE software Four key loops were identified for the dynamic internal marketing model that included customer orientation, knowledge, satisfaction and motivation. And the results showed that if the identified four loops were supported and developed, internal marketing would have a high growth. Among these factors, customer orientation became more important to be achieved by developing a culture of customer orientation in organizations.